Efeito hormético de Verdict® Max na cultura do feijão - Costa, Alan Patrick de Souza (2022)
The culture of the Common Bean (Phaseolus vulgaris L.) has great importance to society, both economically and nutritionally. In turn, it has several benefits for human health, and among them we can mention iron, fiber, mineral salts, potassium, phosphorus and calcium. About 60% of the Brazilian population consumes common bean daily, and for this reason Brazil is one of the largest producers and consumers of common bean in the world. The present work aimed to analyze the possible hormetic effect of the product Verdict® Max in the bean crop, in order to examine the development of the plant after the application of the product, in different doses. The implementation of this work was carried out in the greenhouse of the Universidade Tecnológica Federal do Paraná, campus Dois Vizinhos, in May 2022. One cultivar of Black Bean and another of Carioca Bean were used. They were sown in 12L vases, using five seeds per vase, and three days after the emergence of the crop, thinning was performed, leaving three plants per vase. Irrigation was carried out daily, and the amount of water was defined according to the analysis of each pot, the herbicide application was carried out within the critical period of the crop in V4. For the development of this work, a completely randomized design was carried out, in a bifactorial scheme of two cultivars and five product doses. The treatments were composed of 72.5 mL/ha1 , 145 mL/ha1 , 290 mL/ha1 , 580 mL/ha1 , and 0 mL/ha1 . At seven days after herbicide application, phytotoxicity analyzes were carried out at an interval of seven days, in a period of twentyeight days. At the end of this period, analyzes were carried out, including: plant height, insertion of the first pod and first flower, number of leaves, dry and green matter mass of the aerial part, stem diameter and distance between nodes. The results collected and analyzed did not show the hormetic effect, because only in the internode distance variable there was a significant difference, and in the others this difference was not concluded. There was also the presence of phytotoxicity after the application period, but the plant recovered from this stress.